Possible role for a human adenovirus in the pathogenesis of celiac disease (The Rockefeller University Press, 1984)
Celiac disease in humans is activated by the dietary ingestion of wheat, rye, triticale, barley, and possibly oats. Gliadins in wheat and similar proteins in the other grains are known to activate disease in susceptible individuals. There is a striking association between celiac disease and HLA-B8, -DR3 and/or -DR7, and -DC3. Nonetheless, less than 0.2% of individuals with those serologic HLA specificities develop celiac disease and disease is not always concordant among monozygotic twins. We propose that additional environmental factors may be important in the pathogenesis of celiac disease. To investigate that possibility, we examined a data bank of protein sequences for other proteins that might share amino acid sequence homologies with A- gliadin, an alpha-gliadin component known to activate celiac disease and whose complete primary amino acid sequence is known. These studies demonstrate that A-gliadin shares a region of amino acid sequence homology with the 54-kD E1b protein of human adenovirus type 12 (Ad12), an adenovirus usually isolated from the intestinal tract. The region spans 12 amino acid residues, includes 8 residue identities and an identical pentapeptide, and is hydrophilic in both proteins. Antibody reactive with the 54-kD Ad12 E1b protein cross-reacts with A-gliadin, a 119 amino acid cyanogen bromide peptide of A-gliadin that spans the region of homology and a synthetic heptapeptide of A-gliadin from within the region of homology. We suggest that an encounter of the immune system with antigenic determinants produced during intestinal viral infection may be important in the pathogenesis of celiac disease.